SITE-612 - Poag, C; Watts, A; Cousin, M; Goldberg, D; Hart, D; Miller, K; Mountain, G; Nakamura, Y; Palmer, A; Schiffelbein, P; Tarafa, M; Thein, J; et al. (US Govt. Printing Office; UK distributors, IPOD Committee, NERC, Swindon, 1987)
Site 612 was selected to provide a midslope stratigraphic section along the New Jersey Transect. Its position at the intersection of USGS multichannel seismic Lines 25 and 34 affords excellent correlation of the sedimentary sequences here with seismic sequences recorded on the dense grid of seismic lines crossing this part of the New Jersey margin.-from Author